The one and only Ruby - Applegate, Katherine; Castelao, Patricia (New York, New York : Harper, an imprint of HarperCollinsPublishers, 2023)
"Ruby's story picks up a few months after the events of The One and Only Bob. Now living in a wildlife sanctuary, Ruby's caretaker from the elephant orphanage in Africa where she grew up is visiting. Seeing him again brings back a flood of memories both happy and sad of her life before the circus, and she recounts the time she spent in the African savannah to Ivan and Bob"--
Includes an excerpt from The one and only Ivan.
008-012.
Keywords: Wildlife refuges -- Juvenile fiction; Elephants -- Juvenile fiction; Gorilla -- Juvenile fiction; Dogs -- Juvenile fiction; Novels in verse